2020
DOI: 10.34117/bjdv6n4-043
|View full text |Cite
|
Sign up to set email alerts
|

Calibração do sensor capacitivo de umidade do solo EC-5 em resposta a granulometria do solo

Abstract: A precisão dos sensores capacitivos utilizados na estimativa do teor de água no solo são dependentes das características do solo, necessitando de calibração para sua correção. O objetivo deste estudo foi calibrar o sensor capacitivo EC-5 para a estimativa do conteúdo de água no solo em relação a diferentes granulometria do solo do cerrado. Em condições de laboratório, comparou-se a variação da umidade dos solos Argila Arenosa, Franco Argilo Arenoso e Argila pelo sensor EC-5 e pelo método volumétrico. As amostr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 11 publications
1
1
0
1
Order By: Relevance
“…Our results are consistent with the soil moisture values found by Sena et al (2020) in their study where they evaluated clayey soils. According to Crubelatti (2020), the researcher also obtained a linear result similar to our study with substrates for the production of fruit and vegetables, thus corroborating this new method of electronic humidity measurement and a low-cost Arduino system.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…Our results are consistent with the soil moisture values found by Sena et al (2020) in their study where they evaluated clayey soils. According to Crubelatti (2020), the researcher also obtained a linear result similar to our study with substrates for the production of fruit and vegetables, thus corroborating this new method of electronic humidity measurement and a low-cost Arduino system.…”
Section: Resultssupporting
confidence: 92%
“…In our study, an exhaustive step was observed in programming the sensors according to our evaluation needs, there was the development of MACROS and tables for data conversion. However, our values were on a linear scale according to the sample and its moisture content, which was discussed in the study by Sena et al (2020). With the adjustment line plotted in Figure 5, it is possible to observe the linearity between the values obtained.…”
Section: Resultsmentioning
confidence: 53%
“…Embora os valores de resistividade do solo tenham importância na avaliação da sua corrosividade, existem algumas divergências entre a metodologia de ensaio laboratorial brasileira, descritos nos procedimentos da norma ABNT NBR 16254-1:2014 (Anexo C) e a norma internacional ASTM G 187-15, que podem ocasionar resultados inconsistentes e prejudicar a avaliação do material. Isso pode ocorrer, entre outras questões, devido à variabilidade de características que os solos podem apresentar, cujos parâmetros físicos tendem a afetar as demais propriedades, como reportado por Sena et al (2020), em estudos voltados para o desenvolvimento de sensores capacitivos para a estimativa do teor de água.…”
Section: Introductionunclassified